Analisis Penyebab Tidak Terlaksananya Retensi dan Pemusnahan Berkas Rekam Medis di Rumah Sakit Umum Daerah Natuna - Rizal Hilmansyah (Universitas Duta Bangsa Surakarta, 2021)
Retention/shrinkage and destruction of medical record files is one of the important means to overcome the problem of accumulating files that have no more useful value.This study aims to analyze the causes of inadequate retention and destruction of medical record files at Natuna Hospital. The research method used is a qualitative method. This method is used to investigate, and analyze the causes of non-implementation of retention and destruction of medical record files at Natuna Hospital. The research subjects were medical record file officers / employees at Natuna Hospital. Data collection techniques with observation, interviews and documentation. Data analysis with interactive analysis. The results of this study 1) HR in Natuna Hospital is not enough. The number of officers is 16 people. The level of education is not standard yet because many are high school graduates. The knowledge aspect needs to be improved because it is still low. 2) The infrastructure at Natuna Hospital is not standard. The storage area for medical record files needs to be added and standardized using (rool o pac cupboard) while the retention schedule does not yet exist. 3) Natuna Hospital does not yet have a Standard Operating Procedure. The research suggestion is to create a Standard Operating Procedure so that it becomes the standard reference for officers in the retention and destruction of medical record files.